Factores laborales relacionados a calidad de vida de los cuidadores familiares en el contexto COVID-19 Iquitos 2021 - Eyzaguirre Pfening, Caroline Nicole (2024)
The objective was to determine if there is a relationship between labor factors and the quality of life of family caregivers of older adults in the context of COVID-19 in the city of Iquitos, year 2021. This was quantitative, descriptive, correlational and cross-sectional study. With a sample of 337 family caregivers of older adults in the Senior Citizen Centers of the metropolitan city of Iquitos. The results revealed that more than 50% of the caregivers are under 60 years of age; 63.2% are women; 49.3% have a high school education. Regarding labor factors, 50% have been providing care for a maximum of 6 years, dedicating up to 11 hours daily. Eighty-five percent buy medication, 55.2% carry out daily monitoring, and 44.5% administer it. 17.8% provide support for walking, 14.5% for recreation, and only 3% for personal hygiene. Quality of Life in the context COVID-19, caregivers show low quality of life in dimensions such as Physical function, physical role, bodily pain and emotional role; when analyzing the data, significant differences were demonstrated in the time dedicated between poor and good quality of life with a (p=0.001). The dedication of time and daily hours were significantly related to the quality of life of caregivers (p=0.001). Conclusion: This study allows us to demonstrate that these factors significantly influence the quality of life of family caregivers o folder adults in the context COVID-19.